Teachers’ Understanding in Implementing Multiliteracy Learning in Elementary School (A Comparative Study of Literacy Learning in Indonesia and the Philippines) - Tryanasari, Dewi; Rulviana, Vivi; Widyaningrum, Heny Kusuma; Lestari, Sri; Chasanatun, Fida; Tomas, Mary Jane L.; Adigue, Andrea P. (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the understanding of teachers in Indonesia and the Philippines on multiliteracy learning in primarry school. The sample was 220 primary school teachers in phase C with saturated sampling technique. This study used a questionnaire developed based on Wigin’s taxonomy. The questionnaire was about the understanding of phase C primary school teachers on the basic concepts of literacy and literacy learning. The research method used a quantitative approach with a survey type of research. Based on the questionnaire items that have been done by the teacher, it can be seen that the teacher’s understanding of multiliteracy learning is still lacking. This can be seen from some of the results of correct answers in each statement item still vary. This research can be the basis for improving teachers‘ understanding of multiliteracy learning that can be implemented in elementary schools which is certainly to improve students’ skills in accordance with the development of 21st century skills to form active, creative, innovative and characterised students.